Perception of grain farmers in the Brazilian Cerrado region regarding the adoption or non-adoption of bioinputs - Ricardo Cerveira; Georgia Bertoni Pompeu; Christiano França da Cunha (Contextus)
Background: The adoption and expansion of the use of bioinputs on rural properties appears to be one of the paths to achieving more ecological cultivation and production, based on the three pillars of sustainability: the environment, society and the economy. Therefore, understanding the motivations and barriers that lead rural producers to adopt (or not) and expand (or not) the use of bioinputs is essential.